2005
DOI: 10.1111/j.1463-1318.2005.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Does gum chewing reduce postoperative ileus following open colectomy for left‐sided colon and rectal cancer? – a prospective randomized controlled trial

Abstract: The addition of gum chewing to a standardized postoperative regimen did not reduce the period of postoperative ileus or shorten length of stay following open surgery for left-sided colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 31 publications
3
105
0
4
Order By: Relevance
“…Gastrointestinal hormones, such as gastrin, neurotensin, cholecystokinin and pancreatic polypeptide, are also increased and result in vagal stimulation of smooth muscle fibres. 74 Chewing gum also increases secretion of saliva and pancreatic juices, and a recent study proposed that sorbitol and hexitol found in sugar-free gum may also play a role in the reduction of postoperative ileus. 75 A number of studies exist which demonstrate the benefits in patients undergoing colorectal surgery.…”
Section: Prevention Of Prolonged Postoperative Ileusmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal hormones, such as gastrin, neurotensin, cholecystokinin and pancreatic polypeptide, are also increased and result in vagal stimulation of smooth muscle fibres. 74 Chewing gum also increases secretion of saliva and pancreatic juices, and a recent study proposed that sorbitol and hexitol found in sugar-free gum may also play a role in the reduction of postoperative ileus. 75 A number of studies exist which demonstrate the benefits in patients undergoing colorectal surgery.…”
Section: Prevention Of Prolonged Postoperative Ileusmentioning
confidence: 99%
“…75 A number of studies exist which demonstrate the benefits in patients undergoing colorectal surgery. 73,74,[76][77][78] A meta-analysis of several RCTs evaluating the effect of chewing gum on postoperative ileus has subsequently been published. Although there are relatively low patient numbers and a significant heterogeneity of studies, chewing gum offers significant benefits by reducing the time to pass flatus and the time until first bowel movement.…”
Section: Prevention Of Prolonged Postoperative Ileusmentioning
confidence: 99%
“…The gum was supplied to patients 3 times a day at 8:00 am, 1:00 pm, and 6:00 pm, starting from the day of admission to the ward after surgery; this treatment was based on studies by Quah, et al, [14], Schuster, et al, [10], Bang, et al, [6], and Kim, et al, [15]. The duration of gum chewing was 1 hour, which was based on the studies by Schuster, et al, [10] and Bang et al [6] Gum chewing was discontinued following the self-reporting of the first passage of flatus from the bowel, which was based on certain studies [6,10,14,16,17] wherein oral intake was initiated after the passage of flatus, after which gum chewing was discontinued.…”
Section: Methodsmentioning
confidence: 99%
“…Gum chewing shows immediate post-operative facilitated recovery from ileus following resection for leftsided colorectal cancer. [76] Gum chewing enhances early recovery from POI after laparoscopic colectomy. [77] It reduces ileus after elective open sigmoid colectomy.…”
Section: Clinical Healing Effectsmentioning
confidence: 99%